Diphenyl diselenide, a simple glutathione peroxidase mimetic, inhibits human LDL oxidation in vitro - Bem, Andreza Fabro de (2008)
Oxidative modification of low-density lipoprotein (LDL) represents an important factor in atherogenesis. In the present study, we have investigated the antioxidant capability of diphenyl diselenide (PhSe)2, a simple organoseleno compound, against copper (Cu2+) and peroxyl radical-induced human LDL oxidation in vitro. In initial studies using human serum, (PhSe)2 caused a dose-dependent inhibition of Cu2+-induced lipid peroxidation, which was correlated to thiol consumption. (PhSe)2 increased lipid peroxidation lag phase and decreased lipid peroxidation rate in isolated human LDL, evaluated by measuring both conjugated diene (CD) and thiobarbituric acid reactive substances (TBARS) levels. Consistent with these observations, (PhSe)2 showed a marked inhibitory effect on 2,2-azobis(2-amidinopropane dihydrochloride) (AAPH)-induced oxidation of LDL or parinaric acid (PnA) incorporated into LDL. (PhSe)2 also displayed a dose-dependent protective effect against Cu2+-induced lipid peroxidation in rat aortic slices. Interestingly, besides the antioxidant effects of (PhSe)2 toward the lipid moieties of LDL, which was related to its thiol-peroxidase activity, protein moieties from human isolated LDL were also protected against Cu2+-induced oxidation. The results presented herein are the first to show that (i) (PhSe)2 inhibits lipid peroxidation in human isolated LDL in vitro, (ii) this phenomenon is related to its thiol-peroxidase activity, and (iii) this chalcogen also prevents the oxidation of protein moieties of human LDL. Taken together, such data render (PhSe)2 a promising molecule for pharmacological studies with respect to the atherogenic process.